Development of LLDPE based active nanocomposite films with nanoclays impregnated with volatile compounds - Tornuk, Fatih; Sagdic, Osman; Hancer, Mehmet; Yetim, Hasan (ELSEVIER SCIENCE BV, 2018)
In this study, a novel procedure was performed for grafting of nanoclays (montmorillonite (MMT) and halloysite (HNT)) with essential oil constituents (thymol (THY), eugenol (EUG) and carvacrol (CRV)) using Tween 80 as surfactant and then the nanoclay particles were incorporated into LLDPE pellets (5 wt%) to produce active nanocomposite films using a twin screw extruder. The resulting nanocomposite films were analyzed for antimicrobial and antioxidant capacity as well as thickness, mechanical, color, barrier, thermal properties and surface morphology and molecular composition. Release of the active compounds from the films at the refrigerated and room temperature conditions were also tested. The results showed that the films had strong in vitro antibacterial activity against pathogenic bacteria (Salmonella Typhimurium, Escherichia coli O157:H7, Listeria monocytogenes, Staphylococcus aureus and Bacillus cereus) while their effect against lactic acid bacteria (Lactobacillus rhamnosus and Lb. casei) was limited. The lowest and highest DPPH scavenging ability levels were 65.59% and % 87.92, belonged to THY-MMT and EUG-MMT, respectively. Release of active compounds at 24 degrees C was much more rapid than at 4 degrees C. CRV-HNT and THY-HNT provided slower release than the other films. SEM results showed that nanoclays were uniformly dispersed in the polymer matrix with exceptional agglomerates. Incorporation of the active nanoclays significantly (P > 0.05) improved tensile strength and elongation of the films. The results confirmed that LLDPE based active nanocomposite films could be successfully produced due to its good interaction with MMT and HNT, activated with THY, RUG and CRV.
Keywords: Montmorillonite; Halloysite; Nanocomposite film; Thymol; Eugenol; Carvacrol; LOW-DENSITY POLYETHYLENE; MONTMORILLONITE NANOCOMPOSITES; BARRIER PROPERTIES; CLAY; CHITOSAN; ANTIBACTERIAL; ACID; Food Science & Technology